Domain structure evolution in calcium orthovanadate crystal induced by IR laser irradiation. Issue 1 (19th May 2022) - Shishkina, E. V.; Yuzhakov, V. V.; Akhmatkhanov, A. R.; Pelegova, E. V.; Ivleva, L. I.; Makaev, A. V.; Shur, V. Ya.
Abstract: We have presented the first experimental observation of the domain structure evolution in calcium orthovanadate Ca3 (VO4 )2 single crystals as a result of pulse irradiation by IR laser. The appearance of twins and motion of the existing domain walls have been revealed using optical microscopy and piezoresponse force microscopy. The obtained change in as-grown domain structure has been attributed to the action of pyroelectric field and formation of twin structure. Formation of the twin structure accompanied by crystal cracking in the irradiated area have been attributed to mechanical stresses arising during fast crystal heating and cooling induced by pulse laser irradiation.